MAKTABGACHA YOSHDAGI BOLALARDA IJODKORLIK TUSHUNCHASI VA UNING SHAKLLANISH XUSUSIYATLARI - Qodirova Nozimaxon Qaxramonjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article examines the concept of creativity in preschool children and the features of its formation. Preschool age is the most important period for the formation and development of children's creativity. Creativity is manifested not only in art or artistic activities, but also in children's everyday activities, games and approaches to solving problems. The article focuses on the concept of creativity and how it is formed in children, the main factors affecting this process, as well as the need to develop various activities and creative skills that contribute to the development of creative thinking.